SAT0448 Apremilast treatment and long-term (up to 156 weeks) improvements in dactylitis and enthesitis in patients with psoriatic arthritis: analysis of a large database of the phase iii clinical development program. (15th June 2017) - Gladman, DD; Kavanaugh, A; Gomez-Reino, JJ; Wollenhaupt, J; Cutolo, M; Schett, G; Lespessailles, E; McIlraith, M; Hu, C; Edwards, CJ; Birbara, CA; Mease, PJ
Abstract : Background: Dactylitis and enthesitis, hallmark features of psoriatic arthritis (PsA), may be difficult to manage. PALACE 1, 2, and 3 compared the efficacy and safety of apremilast (APR) with placebo (PBO) in patients (pts) with active PsA despite prior conventional DMARDs and/or biologics. Objectives: Report the impact of long-term APR 30 mg BID (APR30) treatment on dactylitis and enthesitis in pts with active PsA. Methods: Pts were randomized (1:1:1) to PBO, APR30, or APR 20 mg BID (APR20) stratified by baseline (BL) DMARD use (yes/no). After the 24-wk PBO-controlled phase, all pts received APR30 or APR20 and could enroll in long-term follow-up. Data for pts entering the study with pre-existing dactylitis or enthesitis were pooled across PALACE 1–3, as prespecified, to allow for robust analysis. Dactylitis count (number of digits [hands/feet] with dactylitis present [0=absence, 1=presence]; range: 0–20) was used to assess dactylitis improvement. Enthesitis was evaluated based on MASES (range: 0–13), indicating the number of painful entheses out of 13 enthesis sites. Wk 24 analyses used LOCF for missing values and data for early escape pts; Wks 52 and 156 used data as observed. Results: Among pts with dactylitis (n=610) or enthesitis (n=915) at BL and ≥1 post-BL value, BL mean dactylitis counts ranged from 3.2 to 3.4 and MASES ranged from 4.4 to 4.8. At Wk 24, mean change in dactylitis count was −1.8 (APR30) vs −1.3 (PBO) ( P =0.0097); more APR30 pts achieved a dactylitis count of 0 vs PBO pts (Table). Mean change in MASES was −1.3 (APR30) vs −0.9 (PBO) ( P =0.0194); more APR30 pts achieved a MASES of 0 vs PBO pts. Significant effect on enthesitis was confirmed in the PSA-006 (ACTIVE) study of APR in pts with a maximum of 1 previous DMARD treatment, in which the Gladman Enthesitis Index was used, focusing on more peripheral sites of activity: significant effect for APR vs PBO was seen as early as Wk 2, and at Wk 24, mean changes were −1.5 vs −0.5 ( P =0.0032, MMRM). Sustained improvements in dactylitis and enthesitis severity were seen in APR pts at Wk 156 in PALACE 1–3 (Table): for dactylitis, 79.6% achieved a count of 0 and the mean percent change was −83.6%; for MASES, 55.0% of APR pts achieved a score of 0 and the mean percent change was −65.2%. Conclusions: The majority of pts (63%) in PALACE 1–3 had active enthesitis and 42% had dactylitis at BL. APR30 demonstrated early and long-term benefit (up to 156 wks) in treating dactylitis and enthesitis, including resolution of BL disease in many pts. Disclosure of Interest: D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB, A. Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB, J. Gomez-Reino Grant/research support from: Roche and Schering-Plough, Consultant for: BMS, Pfizer, Roche, Schering-Plough, UCB, J. Wollenhaupt Grant/research support from: Abbott, BMS, MSD, Pfizer, UCB, Consultant for: Abbott, BMS, MSD, Pfizer, UCB, M. Cutolo Grant/research support from: Actelion, BMS, Sanofi-Aventis, Consultant for: Actelion, BMS, Sanofi-Aventis, G. Schett Grant/research support from: Abbott, Celgene Corporation, Roche, UCB, Consultant for: Abbott, Celgene Corporation, Roche, UCB, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, Servier, M. McIlraith Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, C. Edwards Grant/research support from: Celgene Corporation, Pfizer, Roche, Samsung, Consultant for: Celgene Corporation, Pfizer, Roche, Samsung, Speakers bureau: Abbott, GSK, Pfizer, Roche, C. Birbara Grant/research support from: Amgen, BMS, Incyte, Eli Lilly, Merck, Pfizer, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Genentech, Janssen, Eli Lilly, Novartis, Pfizer, Roche, UCB, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Genentech, Janssen, Eli Lilly, Pfizer, UCB